Crime & punishment : offenders and victims in a broken justice system - Marks, Russell (Research associate) (Redback, 2015)
Drawing on his experience as a lawyer, Russell Marks makes a case for restorative justice and community correction, whereby offenders are obliged to engage with victims and make amends as an alternative to the present unsatisfactory situation.